If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 = z + -5 Reorder the terms: -8 = -5 + z Solving -8 = -5 + z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. -8 + -1z = -5 + z + -1z Combine like terms: z + -1z = 0 -8 + -1z = -5 + 0 -8 + -1z = -5 Add '8' to each side of the equation. -8 + 8 + -1z = -5 + 8 Combine like terms: -8 + 8 = 0 0 + -1z = -5 + 8 -1z = -5 + 8 Combine like terms: -5 + 8 = 3 -1z = 3 Divide each side by '-1'. z = -3 Simplifying z = -3
| 8z-z=-1+2z-1-3 | | w-4=-12 | | -9=b-3 | | 8z-z=1+2z-1-3 | | -2d-3+4d=8d+45 | | 9x-7/6= | | -3x-2(4x+5)=111 | | 8z-z=1+2z-1-13 | | 2a^2b-5ba^2+13ab= | | 2(17x+3)=(21x+31)+(10x-4) | | (3x+4)=65 | | 8n-7=11+6n | | 3n-19=15+9n | | t^2-20=0 | | 11v-8=27 | | x^4-5x^2+9=0 | | 15.00+2.00x=-11 | | (-x^2)+19x+20=0 | | c^2-6c=2c+20 | | 116=4x+12 | | 3x+7(-x+14)=146 | | 2(3+3x)-5=37 | | 5((3x+4)+2)=65 | | 9+5x=6y | | 0.25y+3=-11 | | 9+5x=9y | | 0.71z+1=11 | | c^2-5c-366=0 | | (a+27)+b=247 | | -9x-6(-9.5122)=54 | | a+b=247 | | 0.6e+7=17 |